EFFECTS OF AVIAN INFLUENZA H5N1 ON POULTRY PRODUCTION IN WUDIL TOWN OF KANO STATE, NIGERIA. - Mohammed, R.; Musa, I. M. (Journal of Agripreneurship and Sustainable Development, 2018)
The study examined the effects of avian influenza H5N1 on poultry production in Wudil town of Kano State, Nigeria. Questionnaires were administered to 40 respondents randomly sampled. Descriptive statistics and farm budgeting techniques were used for data analysis. The study revealed that more than half (67.5%) of the respondents were male with mean age of 38 years. About 65% were married with an average household size of 6 persons. The results indicated that about 77% of the respondents sold between 41-50 crates of eggs before avian influenza outbreak, 94.1% sold less than 10 crates during the epidemic while 50% sold between 31-40 crates after the epidemic. Most (85%) of the respondents used layer birds for production, the estimated mean flock size was 600 birds. Decline in demand of poultry products was realized during the disease outbreak. Poultry producers identified high cost of feed and diseases as their major constraints. It was therefore recommended that poultry producers should be encouraged to form agricultural co-operatives in order to pool resources together and negotiate jointly with input suppliers to limit high cost of production inputs and these cooperatives should also collaborate with ADP’s and Ministry of Agriculture to design training programs for farmers on the precautions and preventive measures of averting the effects of avian influenza on the economy. This will increase the income of poultry producers in the study area.